Assessment of functional, communicative, and critical health literacy in diabetes management among patients attending a tertiary care centre in Maharashtra, India - Mohan, Ajith (International Journal Of Community Medicine And Public Health, 2025)
Background: Effective diabetes management significantly relies on health literacy; however, within the Indian context, its components-communicative, functional, and critical health literacy-are inadequately comprehended. This research aimed to assess the factors related to diabetes treatment for patients enrolled in a tertiary care facility in Maharashtra, India. Methods: Total 201 people under 75 with type two diabetes participated in cross-sectional research. Communicative, Functional, as well as Critical Health Literacy (FCCHL) scale has been employed to evaluate health literacy. Data on sociodemographic factors, diabetes control (last fasting blood sugar values), and health literacy domains were collected and analysed using chi-square tests, odds ratios, and ANOVA. Results: Average participant age was 56.33 yrs (±10.879). Health literacy was higher among men (60.1 percent) than among women (45.1%; p value=0.033). Both functional as well as communicative health literacy didn’t exhibit substantial affiliation with diabetes control; however, critical health literacy did (p equal to 0.008). Health literacy as well as education level were substantially correlated (p=0.043), with graduates showing higher literacy. Health literacy did not significantly correlate with occupation, family type, or place of residence. Conclusions: Better diabetes control is strongly correlated with critical health literacy, underscoring the significance of enabling patients to evaluate and apply medical information critically. To improve diabetes management outcomes, interventions should concentrate on enhancing functional and communicative health literacy, especially among females and populations with decreased levels of education.